2020
DOI: 10.1002/ehf2.12875
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing symptom management in the treatment of chronic heart failure

Abstract: Chronic heart failure (CHF) is a chronic, progressive disease that has detrimental consequences on a patient's quality of life (QoL). In part due to requirements for market access and licensing, the assessment of current and future treatments focuses on reducing mortality and hospitalizations. Few drugs are available principally for their symptomatic effect despite the fact that most patients' symptoms persist or worsen over time and an acceptance that the survival gains of modern therapies are mitigated by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 122 publications
(247 reference statements)
2
32
0
3
Order By: Relevance
“… 5 Second, the barrier of ‘response’ is confusing and misplaced: does ‘response’ mean asymptomatic or merely improved? In our experience, while patients often feel better, they rarely become asymptomatic (NYHA (New York Heart Association) class 1), 12 an observation supported by real-world data even in those receiving ARNI. 13 14 Moreover, we should consider whether a highly subjective and poorly reproducible assessment is appropriate to determine our allocation of life-saving treatments.…”
Section: How Did We Get Here?supporting
confidence: 76%
“… 5 Second, the barrier of ‘response’ is confusing and misplaced: does ‘response’ mean asymptomatic or merely improved? In our experience, while patients often feel better, they rarely become asymptomatic (NYHA (New York Heart Association) class 1), 12 an observation supported by real-world data even in those receiving ARNI. 13 14 Moreover, we should consider whether a highly subjective and poorly reproducible assessment is appropriate to determine our allocation of life-saving treatments.…”
Section: How Did We Get Here?supporting
confidence: 76%
“…17 This finding emphasizes the unmet need for HFrEF treatments that can better control symptoms, especially for patients with WHFEs, given the chronic nature of HF symptoms. 18 Second, psychological comorbidities have very important implications because they are associated with HF progression and poor prognosis and can impact patients' adherence to HF treatments. 19À21 Through the use of validated instruments to screen for depression, generalized anxiety disorder and insomnia, we found that patients with WHFEs experienced psychological comorbidities significantly more often and with greater severity than did patients with NWHFEs.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic heart failure (CHF) is a progressive clinical syndrome that adversely affects the patient's [321] quality of life and mainly affects the elderly; the incidence doubles in men and triples in women with each decade after age 65 [322]. The…”
Section: змішаний стресmentioning
confidence: 99%